Istrebiteli . The Fighters - Penzlin, Eduard (Kievskaia Kinostudia, 1939)
Two men are studying together in the same pilot school. They are best friends and inseparable for most of the times. But Varia's blue eyes separate them and ruined their close friendship. A wise commander instructs the two men to work together so that they can restore this relationship. Will it work?